Transitividade e movimento em relatividade de de Sitter - Sampson Sandia, Almeira del Carmen [UNESP] (2013)
There are currently an agreement that special relativity, whose kinematic is ruled by the Poincaré group, fails near the Planck scale. As a consequence, new kinematics have been proposed. An alternative to those theories is the de Sitter special relativity, which assumes a violation, not of the Lorentz symmetry, but of the translation symmetry. In this theory the cosmological constant appears as a kinematic effect and not as an exotic element ?lling the Universe. Taking into account the appropriate transitivity properties, a new conserved current and a new family of maximizing trajectories are obtained. These trajectories introduce a new notion of motion, given by a combination of translations and proper conformal transformations